INFLUENCE OF MACHINING PARAMETERS ON TOOL WEAR AND MACHINING PERFORMANCE IN HIGH SPEED DUCTILE MODE END MILLING OF SODA LIME GLASS - Amin, A. K. M. Nurul; Konnek, Mohammed (IREP, 2016)
Abstract: Soda lime glass is used extensively in engineering application owing to its high hardness, excellent optical properties, and good corrosion and chemical resistance. Previous studies on ductile mode machining were conducted with the application of negative rake angle of the tool in order to achieve high hydrostatic pressure in the cutting zone to change the material from brittle to ductile state. In this research high speed end milling of glass in a conventional CNC were conducted in order to obtain ductile mode machining. Nevertheless, high speed machining (HSM) may increase the tool wear, especially for the carbide tools used in glass machining. Therefore on line heating of glass surface was carried out to reduce tool wear. In this research, the spindle speed was varied in the range 30000 to 50000 rpm, feed rate in the range 5 to 20 mm/min and depth of cut in the range 5 to 50 µm. The temperature of the soldering gun was maintained at 340°C. Mathematical models were developed for the output responses of average surface roughness (Ra) and tool wear for the two machining conditions, namely, without the application of heat and with the application of heat. It was found from the optimization that, minimum surface roughness and minimum tool wear in the experiment without heat assistance obtained at 41,000 rpm of spindle speed, feed rate of 7.12 mm/min and low depth of cut 5 µm. On the other hand, the suggested conditions for minimum surface roughness and tool wear in heat assisted machining were: spindle speed 38,000 rpm, feed rate 20 mm/min and depth of cut 50 µm. Comparing these two suggested optimum values it appears that the metal removal rate in heat assisted machining would be 26 times that of normal cutting to achieve similar surface roughness and tool wear values. This result shows that heat assisted machining will be more economical as the cost of the solder gun system and consumed electricity is very nominal.